Characterisation and Nanobody Targeting of Essential Cytoskeletal Proteins of Trypanosoma brucei - (:unkn) unknown (My University, 2019)
Kinetoplastid parasites, including trypanosomes and leishmania, are responsible for several diseases of socio-economic and public health importance worldwide. These include the Neglected Tropical Diseases: Sleeping Sickness, Chagas disease and Leishmaniasis, as classified by the World Health Organisation (WHO) and the global wasting disease of animals, Surra, as reported by the Food and Agricultural Organisation of the United Nations (FAO). Animal African Trypanosomiais (AAT) causes the death of 3 million cattle per year in sub-Saharan Africa, with an annual loss of 4.5 billion US dollars to the African economy. Cutaneaous leishmaniasis is a zoonotic disease, with 1.5 million new cases reported globally each year.Trypanosoma brucei is an ancient, early diverging eukaryote, used as a model organism in the laboratory for studying eukaryotic cilia and flagella. Remodelling of the trypanosome cytoskeleton is essential for cell morphology, organelle positioning and division. Study of essential proteins of the cytoskeleton provides insight into intracellular processes and could provide potential targets for therapeutic interventions. Trypanosomes evade the host immune system by periodically changing their external surface coat, which is endocytosed, along with any attached host antibodies, via a structure called the flagellar pocket. TbBILBO1 is a structural protein of the Flagellar Pocket Collar (FPC) that is essential for FPC biogenesis and parasite survival. Due to the importance of TbBILBO1 for the parasite, protein partners were investigated.In my thesis, I describe, firstly, the characterisation of a novel and essential cytoskeletal protein, FPC6, of the FPC/Hook complex of T. brucei; FPC6 is a partner of TbBILBO1. RNAi Knock-down of FPC6 protein leads to rapid cell death in the blood-stream form of the parasite accompanied with a block in endocytosis. Secondly, I describe the purification and intracellular expression of a nanobody (Nb48), raised again
Keywords: African Research